Parents and teachers perspectives on animation films in early music learning experiences for children of Sekolah Kebangsaan Seksyen 9, Shah Alam / Sharifah Farhana Syed Hussin - Syed Hussin, Sharifah Farhana (Faculty of Music, 2016)
Animation films fundamentally changed the ways of teaching and learning music. Information has new value and generates new power. Malaysian children are exposed to modern technological entertainment whether it is on mobile devices, television, video games, animated TV or some other form of popular art and media that creates and enables information pertaining music to be shared easily will remain with us for the foreeseable future. Hence, this paper gives a snapshot of the animation films to music teaching and learning. A researcher will be conducted to collect reviews made by music teachers and parents who think whether animated films will be useful to them and have an impact on children's development of their learning in music.